${〈{r}_{t}^{k}〉}_{\text{S}}$ ${〈{r}_{t}^{k}〉}_{\text{D}}$ $〈{r}_{t}^{k}〉$ $〈{r}_{\infty }^{k}〉$ $k=0$ ${\text{e}}^{-\lambda t}$ $1-{\text{e}}^{-\lambda t}$ 1 1 $k=1$ $\frac{4}{\sqrt{\text{π}}}{\left(Dt\right)}^{1/2}{\text{e}}^{-\lambda t}$ $2\zeta \left(\text{erf}\left(\sqrt{\lambda t}\right)-2\sqrt{\lambda t/\text{π}}{\text{e}}^{-\lambda t}\right)$ $2\zeta \text{erf}\left(\sqrt{\lambda t}\right)$ $2\zeta$ $k=2$ $6Dt{\text{e}}^{-\lambda \text{\hspace{0.17em}}t}$ $6{\zeta }^{2}\left(1-\left(1+\lambda t\right){\text{e}}^{-\lambda t}\right)$ $6{\zeta }^{2}\left(1-{\text{e}}^{-\lambda t}\right)$ $6{\zeta }^{2}$ $k=3$ $\frac{32}{\sqrt{\text{π}}}{\left(Dt\right)}^{3/2}{\text{e}}^{-\lambda t}$ $24{\zeta }^{3}\left(\text{erf}\left(\sqrt{\lambda t}\right)-\frac{2}{\sqrt{\text{π}}}\left({\left(\lambda t\right)}^{1/2}+\frac{2}{3}{\left(\lambda t\right)}^{3/2}\right){\text{e}}^{-\lambda t}\right)$ $24{\zeta }^{3}\left(\text{erf}\left(\sqrt{\lambda t}\right)-\frac{2}{\sqrt{\text{π}}}{\left(\lambda t\right)}^{1/2}{\text{e}}^{-\lambda t}\right)$ $24{\zeta }^{3}$ $k=4$ $60{\left(Dt\right)}^{2}{\text{e}}^{-\lambda t}$ $120{\zeta }^{4}\left(1-\left(1+\lambda t+\frac{1}{2}{\left(\lambda t\right)}^{2}\right){\text{e}}^{-\lambda t}\right)$ $120{\zeta }^{4}\left(1-\left(1+\lambda t\right){\text{e}}^{-\lambda t}\right)$ $120{\zeta }^{4}$